2016
DOI: 10.1038/nature19786
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt carbide nanoprisms for direct production of lower olefins from syngas

Abstract: Lower olefins-generally referring to ethylene, propylene and butylene-are basic carbon-based building blocks that are widely used in the chemical industry, and are traditionally produced through thermal or catalytic cracking of a range of hydrocarbon feedstocks, such as naphtha, gas oil, condensates and light alkanes. With the rapid depletion of the limited petroleum reserves that serve as the source of these hydrocarbons, there is an urgent need for processes that can produce lower olefins from alternative fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
543
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(570 citation statements)
references
References 37 publications
23
543
3
1
Order By: Relevance
“…Typically, iron catalysts need alkali metal promotion to attain desired activity and selectivity. It was reported that the addition of Na is beneficial to olefin production222324. The existence of Na obviously enhances the surface basicity and carburization of iron-based catalyst, making the catalyst very active for CO 2 hydrogenation to light olefins14.…”
mentioning
confidence: 99%
“…Typically, iron catalysts need alkali metal promotion to attain desired activity and selectivity. It was reported that the addition of Na is beneficial to olefin production222324. The existence of Na obviously enhances the surface basicity and carburization of iron-based catalyst, making the catalyst very active for CO 2 hydrogenation to light olefins14.…”
mentioning
confidence: 99%
“…However, only in the past few years has the understanding of the physicochemical signatures of an active Co FTS catalyst developed ( 13 , 14 ). This new understanding has evolved mainly as a result of detailed studies of well-defined model catalysts, often investigated using novel x-ray–based catalyst characterization techniques ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alkali metals, including K, Na and Li [24,26,50], are reported to promote Co 2 C formation in CO hydrogenation reactions. Thus, the formation of cobalt carbide is enhanced in these K-promoted catalysts, and these catalysts had higher selectivity to oxygenates, especially for the catalysts with high potassium composition.…”
Section: Z Wang Et Almentioning
confidence: 99%
“…Therefore, the catalyst favors carbon chain polymerization rather than CO insertion [20]. Recently, several studies on cobalt-based FischerTropsch catalysts or higher alcohol synthesis catalysts have reported the formation of cobalt carbide in the presence of syngas [20][21][22][23][24][25][26]. Pei et al [23] and Bian et al [27] claim that cobalt carbide (Co 2 C) can adsorb CO nondissociatively, and insert the CO to adjacent C x H y species.…”
Section: Introductionmentioning
confidence: 97%